An Investıgatıon Of Profıle Changes In Angle Class I Anomalıes Treated Wıth Extractıon And Nonextractıon - Elif Erbay; Mustafa Ülgen (Galenos Yayinevi, 1995)
In this study, soft and hard tissue profile changes in Angle Class I cases with arch length discrepancy treated with four premolars extractions and without extraction by edgewise technique were investigated. The material of the present investigation consists of 90 pre- and post-treatment orthodontic models and lateral cephalometric radiographs of 45 girls with Angle Class I malocclusion. At the end of this study the following changes were observed; facial profile became more protrusive in the nonextraction cases with minimal arch length discrepancy, facial profile became more retrusive in the borderline extraction cases with mild arch length dicrepancy, and noteworthy alteration did not occur in facial profile of the clear-cut extraction cases with severe arch length discrepancy.